Sarthaks Test
0 votes
628 views
in Mathematics by (15.0k points)

Simplify and solve the linear equation

3( t - 3 ) = 5( 2t + 1)

1 Answer

0 votes
by (24.8k points)
selected by
 
Best answer

3( t - 3 ) = 5( 2t + 1 )

⇒ 3t − 9 = 10t + 5 (Opening the brackets)

⇒ −9 − 5 = 10t − 3t

⇒ −14 = 7t

⇒ t = -14/7

⇒ t = -2

Related questions

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

Categories

...